2022
DOI: 10.1186/s13223-022-00720-z
|View full text |Cite
|
Sign up to set email alerts
|

Childhood allergic diseases across geographical regions of Kandy and Anuradhapura districts of Sri Lanka; where do the rates stand among other regions: experience from Global asthma network Phase 1 study

Abstract: Background Asthma, allergic rhinitis and eczema have been identified as the most prevalent childhood allergic diseases. However, the prevalence of these allergic diseases can vary in different regions within a country and in the world. Methods The objective of the study was to estimate the prevalence of asthma, allergic rhinitis and eczema in schoolchildren in the Kandy and Anuradhapura districts of Sri Lanka. This was a multicentre cross sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Anuradhapura Medical Journal 2023| Volume 17 | Issue 2 | Page |4-10 years (1.21%; 95%CI 0.18%-2.24% per decade) compared to adolescents aged 13-14 years (0.98%; 95%CI 0.014%-1.92%) [17]. Furthermore, a study comparing the prevalence of eczema among adolescents aged 13-14 years from the Anuradhapura and the Kandy districts reported a lower prevalence in the Anuradhapura district (1.8%; 95%CI 1.38-2.34) compared to the Kandy district (7.3%; 95%CI 6.15-8.65) [18]. However, the current study reports a significantly higher prevalence of eczema among adolescents aged 13-14 years from the Anuradhapura (p<0.01) which may be because the current study was conducted in the municipal council area.…”
Section: Open Accessmentioning
confidence: 97%
“…Anuradhapura Medical Journal 2023| Volume 17 | Issue 2 | Page |4-10 years (1.21%; 95%CI 0.18%-2.24% per decade) compared to adolescents aged 13-14 years (0.98%; 95%CI 0.014%-1.92%) [17]. Furthermore, a study comparing the prevalence of eczema among adolescents aged 13-14 years from the Anuradhapura and the Kandy districts reported a lower prevalence in the Anuradhapura district (1.8%; 95%CI 1.38-2.34) compared to the Kandy district (7.3%; 95%CI 6.15-8.65) [18]. However, the current study reports a significantly higher prevalence of eczema among adolescents aged 13-14 years from the Anuradhapura (p<0.01) which may be because the current study was conducted in the municipal council area.…”
Section: Open Accessmentioning
confidence: 97%
“…In 2021, Liu showed that allergic diseases increased the severity of TD childhood (48). In 2022, a meta-analysis provided strong evidence for a relationship between allergic diseases and TD: TD is positively associated with AA, AR, and AC (21). In 2022, Zhang et al showed some concordance with TD in the grading and distribution of IgE and sIgE levels in children with allergic diseases (49).…”
Section: Correlation Between Allergic and Tdmentioning
confidence: 99%
“…Over the past 20 years, the prevalence of childhood allergic diseases has been increasing globally ( 20 , 21 ), already affecting about 25% of children ( 22 ). In 2010, the occurrence of FA among children in the US stood at 8.0% ( 23 ), while in 2019, the prevalence of FA among children aged 2 years and below in Wenzhou, China, escalated to 11.1% ( 24 ).…”
Section: Epidemiologymentioning
confidence: 99%